Denosumab and the Rebound Effect: Current Aspects of Osteoporosis Therapy (Review) - N. Yu. Velts; O. V. Velts; R. N. Alyautdin (Безопасность и риск фармакотерапии)
INTRODUCTION. Osteoporosis is a leading cause of morbidity, disability, reduced quality of life, and premature mortality in the elderly population. Denosumab is a treatment for osteoporosis; however, denosumab discontinuation may cause a rebound effect, which is a severe adverse drug reaction (ADR) leading to an increase in the rate of bone tissue loss. Studying the mechanism of the rebound effect and potential ways to manage it can improve the safety of denosumab therapy.AIM. This study aimed to summarise up-to-date information regarding the mechanism of the rebound effect and ways to manage it after denosumab discontinuation.DISCUSSION. Osteoporosis results from an imbalance in bone remodelling. Recent studies have shown that mature osteoclasts are able to fission into osteomorphs, which separate from the polykaryon and fuse with neighbouring osteoclasts or other osteomorphs (osteoclast recycling). The mechanism of action of denosumab is based on the inhibition of osteoclast recycling, which results in the accumulation of pre-osteoclasts and osteomorphs. Research into processes occurring in bone tissue shows that denosumab creates a pool of induced cells, and when denosumab therapy is discontinued, these induced cells quite quickly and abundantly differentiate into osteoclasts causing bone resorption (rebound effect) and increasing the risk of fractures. In order to improve mineral bone density and to prevent fractures after denosumab discontinuation, it is reasonable to use antiresorptive medicines from the bisphosphonate class. Bisphosphonates accumulate in bone tissue and concentrate in areas of active bone metabolism.CONCLUSIONS. Further studies of the rebound effect mechanism, including a deeper understanding of the role of osteomorphs in osteogenesis, will improve the measures taken to reduce the risk of fractures after denosumab discontinuation. Further research is needed to evaluate the effect of antiresorptives on bone tissue loss after denosumab discontinuation.